STRENGTHENING THE POSITION OF INTELLECTUAL CAPITAL AND KNOWLEDGE MANAGEMENT IN HUMAN RESOURCE MANAGEMENT: AN OVERVIEW - Sutangsa Sutangsa; Jihan Jihan; Herman Rustandi; Nelli Roza; Didi Pianda (Komitmen: Jurnal Ilmiah Manajemen, 2023)
Changes in intellectual capital as well as knowledge management occur as a result of technological and information developments. These changes then affect human resource management in various ways. This research looked at how intellectual capital and knowledge management can influence the development of human resource management. This research will be carried out using a qualitative approach. The data used in this study is secondary data derived from various research results and previous studies. The results of this study then found that human resource management is very important in digital technology because companies need to develop according to the current era. Therefore, people who work in the shadows as people in charge of human resource management need to have strong intellectual capital and knowledge management. The existing human resource management can develop properly by having these two things.